Copper(II)-mediated synthesis of indolequinones from bromoquinones and enamines - Inman, Martyn; Moody, Christopher J. (Wiley-VCH Verlag, 2013)
The reaction of enamines and bromoquinones in the presence of copper(II) acetate and potassium carbonate results in a regiospecific synthesis of indolequinones. The reaction is broad in scope and scalable and provides a route to the core structure that is present in several biologically interesting natural and synthetic compounds.